Using mHealth Tools to Improve Rural Diabetes Care Guided by the Chronic Care Model - Jennifer A Mallow; Laurie A Theeke; Emily R Barnes; Tara Whetsel; Brian K Mallow (Rural Nurse Organization; Binghamton University, 2014)
Background and objective: Used as an integrated tool, mHealth may improve the ability of healthcare providers in rural areas to provide care, improve access to care for underserved populations, and improve biophysical outcomes of care for persons with diabetes in rural, underserved populations. Our objective in this paper is to present an integrated review of the impact of mHealth interventions for community dwelling individuals with type two diabetes. Materials and methods: A literature search was performed using keywords in PubMed to identify research studies which mHealth technology was used as the intervention Results and discussion: Interventions using mHealth have been found to improve outcomes, be cost effective, and culturally relevant. mHealth technology that has been used to improve outcomes include: seeking out health information via the web, access to appointment scheduling and medication refills, secure messaging, computerized interventions to manage a chronic condition, use of a personal health record, use of remote monitoring devices, and seeking support from others with similar health concerns through social networks. Conclusion: Using the validated Chronic Care Model to translate what is known about mHealth technology to clinical practice has the potential to improve the ability of healthcare providers in rural areas to provide care, improve access to care for underserved populations, and improve biophysical outcomes of care for persons with diabetes in rural underserved populations. While these approaches were effective in improving some outcomes, they have not resulted in the establishment of the necessary electronic infrastructure for a sustainable mobile healthcare delivery model. DOI:  http://dx.doi.org/10.14574/ojrnhc.v14i1.276  Key Words: mHealth, Rural, Diabetes, Chronic Care model